Aggregate risk assessment of polycyclic aromatic hydrocarbons from dust in an urban human settlement environment. (1st October 2016) - Xu, Linyu; Shu, Xin; Hollert, Henner
Abstract: Due to the coal-dominated energy structure and increasing numbers of vehicles, gaseous polycyclic aromatic hydrocarbons (PAHs) emissions are increasing in many cities in China. These emissions have the potential to threaten human health, especially when aggregated in human settlement environments located in areas of rapid industrialization and urbanization. In this paper, an urban aggregating health risk assessment framework based on a multiple-pathways exposure model, dose–risk relationships and scenario analysis, using dust as an environmental medium is proposed and examined for future study. In a case study of Nanjing, several dust samples were collected from different functional areas and the aggregate risk of polycyclic aromatic hydrocarbons in each sampling unit was assessed. The results indicated that non-carcinogenic risk and carcinogenic risk in Nanjing are currently acceptable, but cannot be ignored in the long term. The carcinogenic risk in the west of Nanjing was relatively high, but still acceptable, while it was lower in central and southeast Nanjing and lowest in the northeast. These results can be further utilized for urban planning. Future urban construction in Nanjing, especially residential construction, should be expanded to the south of the city rather than the west, to minimize the human health risk caused by industries. Highlights: Dust is used as an environmental medium. A multiple-pathways exposure model combined is implemented in a case study. An urban aggregating health risk assessment framework is proposed and examined.